2015
DOI: 10.1021/acs.jpclett.5b00909
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Exciton Dynamics in InGaN/GaN and Rh/Cr2O3 Nanoparticle-Decorated InGaN/GaN Nanowires

Abstract: Ultrafast exciton and charge-carrier dynamics in InGaN/GaN nanowires (NWs) with and without Rh/Cr2O3 nanoparticle (NP) decoration have been investigated using femtosecond transient absorption (TA) techniques with excitation at 415 nm and white-light probe (450-700 nm). By comparing the TA profiles between InGaN/GaN and InGaN/GaN-Rh/Cr2O3 NWs, an additional decay component on the medium time scale (∼50 ps) was identified with Rh/Cr2O3 decoration, which is attributed to interfacial charge transfer from InGaN/GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…Before the detailed study of the exciton decay dynamics, we performed TA/TB measurements of the CdS and CdS/TiO 2 samples under three different pump powers of 230 nJ per pulse, 140 nJ per pulse, and 73 nJ per pulse to determine the possible power dependence of the dynamics since power dependent dynamics due to the nonlinear process can affect the interpretation of the results. [36][37][38][39] As shown in Fig. 7, the normalized maximum TB proles of each sample represented a relatively signicant difference as the pump power increased, however, the most similar recovery traces at a fast recovery component on a short time scale (0-20 ps) of all samples (insets of Fig.…”
Section: Charge Carrier Dynamics By Transient Absorption Spectroscopymentioning
confidence: 81%
“…Before the detailed study of the exciton decay dynamics, we performed TA/TB measurements of the CdS and CdS/TiO 2 samples under three different pump powers of 230 nJ per pulse, 140 nJ per pulse, and 73 nJ per pulse to determine the possible power dependence of the dynamics since power dependent dynamics due to the nonlinear process can affect the interpretation of the results. [36][37][38][39] As shown in Fig. 7, the normalized maximum TB proles of each sample represented a relatively signicant difference as the pump power increased, however, the most similar recovery traces at a fast recovery component on a short time scale (0-20 ps) of all samples (insets of Fig.…”
Section: Charge Carrier Dynamics By Transient Absorption Spectroscopymentioning
confidence: 81%
“…Surface reaction sites are essential for carrier transportation and GaN materials’ photostability. Pu et al have shown that Rh/Cr 2 O 3 nanoparticles equipped InGaN/GaN nanowires with additional charge decay pathways can increase overall water splitting efficiency [ 13 ]. However, this efficiency is not comparable to that of materials such as SnO 2 and TiO 2 , because of the relatively low light absorption ratio of GaN materials [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…further investigated the charge carriers dynamics of InGaN/GaN NWs with loading Rh/Cr 2 O 3 core/shell nanoparticles. [ 141 ] The ultrafast femtosecond pump‐probe laser spectroscopy and a kinetic model demonstrate Rh/Cr 2 O 3 develops the medium time scale (≈50 ps) of exciton decay compared to excitation relaxation (≈33 ps) and excitation recombination (≈167 ps), which is attributed to the large k tran from the CB of InGaN/GaN NWs to Rh/Cr 2 O 3 nanoparticles and thus achieve the enhanced charge separation in InGaN/GaN NWs (Figure 8d). Chu et al.…”
Section: Recent Advances Of Surface/interface Structure Modulation Onmentioning
confidence: 99%
“…Reproduced with permission. [ 141 ] Copyright 2015, American Chemical Society. e) Energy band structure and PEC reaction scheme of the photoanodes.…”
Section: Recent Advances Of Surface/interface Structure Modulation Onmentioning
confidence: 99%